2019
DOI: 10.18332/ejm/111802
|View full text |Cite
|
Sign up to set email alerts
|

Learning experiences of final-year student midwives in labor wards: A qualitative exploratory study

Abstract: INTRODUCTION Clinical placements are an integral part of midwifery education and are crucial for achieving professional competencies. Although students’ experiences on placements have been shown to play a meaningful role in their learning, they have received scant attention in the literature. The aim of this paper is to describe the learning experiences of final-year student midwives in labor wards within the Brussels metropolitan region, Belgium. METHODS A qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This result indicated that midwifery students complained, some staffs' were ordered them to be outside of the room while they were performing complicated procedures like repairing perineal-tear and resuscitating neonates. This is in line with a study conducted in Belgium and Iran; in the case of pathologies like post-partum bleeding, preceptors and staffs didn't explain what is going to be done and why rather they pushed aside for the students that lead midwifery students not to participate in such acute and real situations and make them demotivated to learn (19,23).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result indicated that midwifery students complained, some staffs' were ordered them to be outside of the room while they were performing complicated procedures like repairing perineal-tear and resuscitating neonates. This is in line with a study conducted in Belgium and Iran; in the case of pathologies like post-partum bleeding, preceptors and staffs didn't explain what is going to be done and why rather they pushed aside for the students that lead midwifery students not to participate in such acute and real situations and make them demotivated to learn (19,23).…”
Section: Discussionsupporting
confidence: 75%
“…But contradicted with a study conducted in Belgium and Ireland; students stressed the need for continuity of clinical preceptor during clinical placements. This helped midwifery students to have trust, create connections, and to develop professional relationships which in return help them to see their progress based on their clinical preceptor's follow up and constructive feedback (23,26). This might be due to differences in assignment, quali cation, and using of clinical preceptor.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Units that are overcrowded because of student midwives from different nursing education institutions (NEIs) and lack of time have also resulted in non-completion of skills. [4,5] The increased number of midwifery students in maternity units has created a competitive atmosphere. [5] Furthermore, student midwives' personal issues such as family responsibilities and transport problems have hindered experiential learning and the completion of the midwifery register.…”
Section: Researchmentioning
confidence: 99%
“…[4,5] The increased number of midwifery students in maternity units has created a competitive atmosphere. [5] Furthermore, student midwives' personal issues such as family responsibilities and transport problems have hindered experiential learning and the completion of the midwifery register. [6] All these factors have impacted negatively on skills achievement and completion of the register.…”
Section: Researchmentioning
confidence: 99%
“…Learning in the clinical environment allows midwifery students to learn by gaining practical experience (Ball et al, 2022). However, studies showed that clinical practice environment may have a positive or negative impact on learning and professional development of the student (Arundell et al, 2018; Capper et al, 2021; Vermeulen et al, 2019). During clinical practice midwifery students live the reality of the practice, interact with fellow health professionals and patients, and develop their professional identity.…”
Section: Introductionmentioning
confidence: 99%